A New Class of Organic Crystals with Extremely Large Hyperpolarizability: Efficient THz Wave Generation with Wide Flat-Spectral-Band - Kim, Seung Jun; Yu, In Cheol; Kim, Dong Joo; Jazbinsek, Mojca; Yoon, Woojin; Yun, Hoseop; Kim, Dongwook; Rotermund, Fabian; Kwon, O. Pil (Advanced Functional Materials, 2023)
In organic π-conjugated crystals, enhancing molecular optical nonlinearity of chromophores (e.g., first hyperpolarizability β ≥ 300 × 10−30 esu) in most cases unfortunately results in zero macroscopic optical nonlinearity, which is a bottleneck in organic nonlinear optics. In this study, a new class of nonlinear optical organic crystals introducing a chromophore possessing an extremely large first hyperpolarizability is reported. With newly designed 4-(4-(4-(hydroxymethyl)piperidin-1-yl)styryl)-1-(pyrimidin-2-yl)pyridin-1-ium (PMPR) chromophore, incorporating a head-to-tail cation-anion OHO hydrogen-bonding synthon and an optimal selection of molecular anion into crystals results in extremely large macroscopic optical nonlinearity with effective first hyperpolarizability (Formula presented.) of 335 × 10−30 esu. This is in sharp contrast to zero (Formula presented.) value for previously reported analogous crystals. An ultrathin PMPR crystal with a thickness of ≈10 µm exhibits excellent terahertz (THz) wave generation performance. Both i) broadband THz wave generation with a wide flat-spectral-band in the range of 0.7–3.4 THz defined at −3 dB and high upper cut-off generation frequency of > 7 THz as well as ii) high-generation efficiency (5 times higher THz amplitude than ZnTe crystal with a mm-scale thickness) are simultaneously achieved. Therefore, new PMPR crystals are highly promising materials for diverse applications in nonlinear optics and THz photonics.
Keywords: Electro-optics; First hyperpolarizabilities; Hyperpolarizabilities; Optical nonlinearity; Organic crystal; Spectral band; Tera Hertz; Terahertz photonics; Terahertz wave generation; Terahertz-wave generation; electro-optics; nonlinear optics; THz photonics